Slovensko pravorečje kot samostojna kodifikacijska knjiga? - Tivadar, Hotimir (Slavia Centralis, 2020)
Slovene Orthoepy as an Independent Codifying Book? Slovene orthoepy is not sufficiently considered within Slovene linguistics, being taken into consideration only within dictionaries for the written language and orthographies and grammar books for experts. Public appearance in Slovene language is these days a must and a reality for almost every speaker that operates within Slovenia, which means that us linguists will have to dedicate ourselves to Slovene public speech and not leave it to spontaneous action and personal linguistic feel. In the article, we justify the need to issue a modern (academic) orthoepy, based on the codification tradition, modern research and the description of speech from modern public texts.